2016
DOI: 10.1021/acs.iecr.6b03265
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ru/ZrO2 Catalysts by NaBH4 Reduction and Their Catalytic Activity for NH3 Decomposition To Produce H2

Abstract: ZrO 2 -supported Ru catalysts were prepared by an impregnation method and by NaBH 4 reduction from RuCl 3 •3H 2 O and a commercial ZrO 2 support. The catalyst prepared by NaBH 4 reduction showed high activity (around 60%) at 673 K for NH 3 decomposition, whereas the catalyst prepared by the impregnation method exhibited low activity (10%) under the same reaction conditions. X-ray fluorescence spectrometry indicated that the catalyst prepared by NaBH 4 reduction was free of Cl, whereas the catalyst prepared by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…us, catalysts that do not require H 2 pretreatment before NH 3 decomposition are highly desirable. As reported previously (Furusawa et al, 2016b), a Ru/ ZrO 2 catalyst prepared by NaBH 4 reduction catalyzed NH 3 decomposition without H 2 pretreatment because Ru metal was formed by NaBH 4 reduction. erefore, the as-prepared Ru/ZrO 2 catalyst or the Ru/ZrO 2 catalyst treated with Ar (773 K, 1 h) could be used without H 2 pretreatment.…”
Section: Catalytic Performance Of the Ru/ceo 2 Catalystsupporting
confidence: 57%
See 2 more Smart Citations
“…us, catalysts that do not require H 2 pretreatment before NH 3 decomposition are highly desirable. As reported previously (Furusawa et al, 2016b), a Ru/ ZrO 2 catalyst prepared by NaBH 4 reduction catalyzed NH 3 decomposition without H 2 pretreatment because Ru metal was formed by NaBH 4 reduction. erefore, the as-prepared Ru/ZrO 2 catalyst or the Ru/ZrO 2 catalyst treated with Ar (773 K, 1 h) could be used without H 2 pretreatment.…”
Section: Catalytic Performance Of the Ru/ceo 2 Catalystsupporting
confidence: 57%
“…e catalysts were characterized as described in our previous study (Furusawa et al, 2016b). Brie y, X-ray uorescence spectrometry (XRF; ZSX primus II, Rigaku Co.) was employed to determine the quantities of Ru and Cl in the catalysts.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the result of CO chemisorption in Table , the Ru particles average sizes derived from CO chemisorption are obviously bigger than that observed from TEM, which often can be explained by the fact that the residual of Cl – will restrain the chemisorption of CO, leading to the overly high valuation for Ru particles . Though the residual of Cl – would attenuate the catalytic performance for the electron-withdrawing effect of Cl – to Ru, RuCl 3 precursor is still thought to be the best alternative for its cheapness and excellent solubility in water . Additionally, the Ru particles size and shape are also thought to have a strong connection with the catalytic performance for NH 3 decomposition because this reaction is a typical structure-sensitive reaction.…”
Section: Resultsmentioning
confidence: 88%
“…49 Though the residual of Cl − would attenuate the catalytic performance for the electron-withdrawing effect of Cl − to Ru, RuCl 3 precursor is still thought to be the best alternative for its cheapness and excellent solubility in water. 50 Additionally, the Ru particles size and shape are also thought to have a strong connection with the catalytic performance for NH 3 decomposition because this reaction is a typical structuresensitive reaction. Garci ́a-Garci ́a et al 51 found that the socalled B5 sites are responsible for the real active sites available to ammonia decomposition, and Ru particles with a diameter The morphology of BHA and Ru particles supported on BHA after reduction at 500 °C for 2.0 h are shown in Figure 6.…”
Section: ■ Results and Discussionmentioning
confidence: 99%